The formation of general instrumental competence of engineering-teachers based on computer information-training method: practical results - Yaschun, T. V; Gromov, E. V; Danica, P. S. (Problems of Engineer-Pedagogical Education, 2019)
The general historical process of informatization covers all facets of society. Computer information and educational tools are tightly integrated into the educational process. A personal computer uses not only as a source of information, but also a system of monitoring and evaluation, a simulator of practical skills, means of conducting scientific and pedagogical research, etc. Its use extends to all stages of the educational process, from the presentation of educational material and to the analysis of the results of acquired knowledge. The level of proficiency in computer information technologies of modern teachers is rapidly growing, there is a significant amount of copyright software development that meets the goals and objectives of a specific learning process. The authors of the work propose a complex of computer-based informationteaching tools, which covers all stages of training, meets modern requirements and contributes to the formation of the general instrumental competence of future engineers-pedagogues of the specialty “Professional education” during basic computer training. The complex includes four software developments: a frontal automated collective control system on a single PC as a technical tool for expanding feedback to enhance interactivity during lectures, a software package for visual programming based on virtual robot control tasks as a system for learning the basics of programming and algorithms, multimedia automated information adaptive training system in C#; simulator skills for effective and high-quality typing and formatting texts in modern office products. The article analyzes the background and features of the development of the presented software development. Technical implementation and their functionality are described. The experimental study allowed us to statistically substantiate the proposed hypothesis about the effectiveness of the formation of the general instrumental competence of engineers-pedagogues on the basis of the proposed approach.